An extrudable heat resistant material, articles made therefrom and uses thereof
Patent Information
- Application Number
- CN202311185000.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-14
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-09-14
AI Technical Summary
但是PVC存在使用方面的局限:一、力学性能差,无法满足高强度结构部件的材料要求;二、耐热性差,其热球压仅为70℃左右,远远达不到家用电器载流部件125℃球压要求
[0063]本公开选用非结晶树脂作为第一基体树脂成分并添加高温结晶树脂作为第二基体树脂成分,同时加入低熔点玻璃粉和膨胀石墨,低熔点玻璃粉在材料中形成高刚性的三维自支撑网络结构,膨胀石墨沿着三维自支撑网络结构富集分布形成三维导热网络结构,解决了异型材挤出时产品易变形,尺寸不稳定的问题。通过本公开方法采用所述耐热材料制备得到的异型材具有耐热性高、导热性好、挤出速率快、高温稳定性强、无变形塌陷等外观缺陷的优点。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This disclosure relates to an extrudable heat-resistant material, articles thereof, and applications. The extrudable heat-resistant material of this disclosure has advantages such as high heat resistance, ease of molding, and excellent dimensional stability, and is suitable for extruded parts, such as insulating strips inside track sockets, and profiled parts like guide rail light rails. Background Technology
[0002] Extrusion molding is a molding method in which heated and molten polymer materials are forced through a die by a screw to form a continuous profile with a constant cross-section. Based on the different cross-sectional shapes of the extruded products, they are classified into pipes, rods, plates, sheets, and irregularly shaped profiles. Among these, irregularly shaped profiles, due to their complex and irregular shapes, require higher material forming performance.
[0003] Non-crystalline plastics (such as PVC) exhibit excellent dimensional stability, making them particularly suitable for profile extrusion. Due to its resistance to deformation in its softened state, PVC possesses strong plastic deformation capabilities, similar to modeling clay, and excellent cooling and setting abilities, making it one of the preferred plastic raw materials in the profile extrusion industry. However, PVC has limitations in its application: firstly, its poor mechanical properties prevent it from meeting the material requirements of high-strength structural components; secondly, its poor heat resistance, with a hot-bulb pressure of only around 70°C, far below the 125°C hot-bulb pressure requirement for current-carrying components in household appliances. Non-crystalline plastics with higher heat resistance (such as PC) generally have poor molding capabilities, and the extrusion process is prone to abnormal phenomena such as profile bending deformation, shrinkage marks, and localized corner collapse, severely affecting the quality of profile extrusion.
[0004] Crystalline plastics (such as PA66) have a fixed melting point and a narrow melting temperature range. Near the melting point, the flow properties of the melt are affected by both temperature and shear stress, resulting in significantly nonlinear melt rheological properties, which greatly complicates stable extrusion molding. Furthermore, crystalline plastics exhibit significant shrinkage due to crystallization, and the presence of post-crystallization and secondary crystallization makes it difficult to mold parts with small dimensional tolerances and high precision, especially complex profiles.
[0005] Therefore, there is an urgent need in this field to develop a heat-resistant material that can be precisely extruded to meet the requirements of profile extrusion, which can form profiles with good heat resistance, strong forming ability, no forming defects and good dimensional stability. Summary of the Invention
[0006] The first aspect of this disclosure provides a heat-resistant material comprising a first matrix resin, a second matrix resin, glass powder, expanded graphite, and optional other additives.
[0007] In a preferred embodiment of this disclosure, the first matrix resin is a non-crystalline resin with high heat resistance, and the second matrix resin is a high-temperature crystalline resin, wherein the peak crystallization temperature of the second matrix resin is higher than the softening point temperature of the first matrix resin.
[0008] In yet another preferred embodiment of this disclosure, the first matrix resin is at least one amorphous resin selected from the group consisting of: polycarbonate (PC), polyphenylene ether (PPO), polycarbonate and acrylonitrile-styrene-butadiene copolymer (PC / ABS), polycarbonate and acrylonitrile-styrene-acrylate copolymer (PC / ASA), styrene-maleic anhydride random copolymer (SMA), engineering plastic grade polyurethane (TPU), poly(4,4-isopropylidene biphenyl terephthalate / isophthalate copolymer (PAR), bisphenol A type polysulfone (PSF), polyethersulfone (PES), and polyphenylene sulfone (PPSU).
[0009] In yet another preferred embodiment of this disclosure, the second matrix resin is at least one high-temperature crystalline resin selected from the group consisting of: polyphenylene sulfide (PPS), poly(1,4-cyclohexanedimethyl terephthalate) (PCT), thermotropic liquid crystal polymer (TLCP), polyhexamethylene adipamide (PA66), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), syndiotactic polystyrene (SPS), and polyetheretherketone (PEEK).
[0010] In yet another preferred embodiment of this disclosure, the additives include compatibilizers, antioxidants, and lubricants.
[0011] In yet another preferred embodiment of this disclosure, the compatibilizer is at least one compound selected from the group consisting of: styrene-maleic anhydride random copolymer (SMA), ethylene-methyl acrylate-glycidyl methacrylate terpolymer (EMA-g-GMA), maleic anhydride-grafted ethylene propylene diene monomer (EPDM-g-MAH), and maleic anhydride-grafted ethylene-1-octene copolymer (POE-g-MAH).
[0012] In yet another preferred embodiment of this disclosure, the glass powder is a low melting point glass powder with a softening point temperature of 250-350°C.
[0013] In yet another preferred embodiment of this disclosure, the glass powder is pretreated with a coupling agent containing amino functional groups; and / or the expanded graphite is pretreated with a coupling agent containing epoxy functional groups.
[0014] In yet another preferred embodiment of this disclosure, the coupling agent containing an amino functional group includes γ-aminopropyltriethoxysilane, 3-aminopropylmethyldiethoxysilane, 3-aminopropylmethyldimethoxysilane, and N-β-(aminoethyl)γ-aminopropylmethyldiethoxysilane; and / or the coupling agent containing an epoxy functional group includes 3(2,3-epoxypropoxy)propyltrimethoxysilane, 3-(2,3-epoxypropoxy)propylmethyldiethoxysilane, and 3(2,3-epoxypropoxy)propyltriethoxysilane.
[0015] In yet another preferred embodiment of this disclosure, the heat-resistant material comprises:
[0016]
[0017] A second aspect of this disclosure provides an article prepared using the heat-resistant material described herein.
[0018] In a preferred embodiment, the article is a profile prepared by extruding a heat-resistant material.
[0019] A third aspect of this disclosure provides the use of a combination of glass powder and expanded graphite in improving the extrusion stability and / or molding capability of materials. Detailed Implementation
[0020] The inventors of this disclosure discovered that by using an amorphous resin as the first matrix resin component and adding a high-temperature crystalline resin as the second matrix resin component, along with low-melting-point glass powder and expanded graphite, theoretically, the low-melting-point glass powder can form a highly rigid, three-dimensional self-supporting network-like structure in the material, and the expanded graphite can accumulate and distribute along this structure to form a three-dimensional thermally conductive network-like structure. This solves the problem of easy deformation and dimensional instability of products during profile extrusion. Based on this, this disclosure was completed.
[0021] The extrudable heat-resistant material disclosed herein comprises a first matrix resin, a second matrix resin, glass powder, expanded graphite, and optional other additives.
[0022] The components of the extrudable heat-resistant material of this disclosure are described in detail below:
[0023] First matrix resin
[0024] The first matrix resin used in this disclosure is a non-crystalline resin with high heat resistance, such as polycarbonate (PC), polyphenylene ether (PPO), polycarbonate and acrylonitrile-styrene-butadiene copolymer alloy (PC / ABS), polycarbonate and acrylonitrile-styrene-acrylate copolymer alloy (PC / ASA), styrene-maleic anhydride random copolymer (SMA), engineering plastic grade polyurethane (TPU), poly(4,4-isopropylidene biphenylene terephthalate / isophthalate copolymer (PAR), bisphenol A type polysulfone (PSF), polyethersulfone (PES), and polyphenylene sulfone (PPSU).
[0025] A non-crystalline resin with high heat resistance is selected as the first matrix resin component. High heat resistance means that the ball pressure heat resistance test can pass 125℃. The ball pressure heat resistance test method is found in standard GB / T5169.21 Fire Hazard Testing for Electrical and Electronic Products Part 21: Abnormal Hot Ball Pressure Test. The first matrix resin component provides heat resistance while ensuring the extruded profile has basic dimensional stability and imparts good mechanical strength and electrical insulation properties to the material.
[0026] Based on the total weight of the heat-resistant material, the amount of the first matrix resin is 60-90% by weight, preferably 62-88% by weight, and more preferably 70-80% by weight.
[0027] Second matrix resin
[0028] The second matrix resin is a high-temperature crystalline resin, possessing the ability to crystallize at higher temperatures, with a crystallization initiation temperature higher than the viscous flow temperature of the first matrix resin. The crystallization initiation temperature is the initial temperature at which the polymer chains of the crystalline polymer begin to align in an orderly manner and are arranged into the crystal lattice with high regularity during the melt cooling process. The viscous flow temperature is the transition temperature of the polymer from a highly elastic state to a viscous flow state. By adding a high-temperature crystalline resin as a component of the second matrix resin, during cooling and shaping, the second matrix resin in the mixed melt, due to its higher crystallization temperature, cools and solidifies before the first matrix resin, giving the profile excellent cooling and shaping capabilities, thereby improving the profile forming ability.
[0029] The second matrix resin includes polyphenylene sulfide (PPS), poly(1,4-cyclohexanediol) terephthalate (PCT), thermotropic liquid crystal polymer (TLCP), polyhexamethylene adipamide (PA66), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), syndiotactic polystyrene (SPS), and polyetheretherketone (PEEK). The specific second matrix resin can be flexibly selected based on the type of the first matrix resin. Generally, the peak crystallization temperature of the high-temperature crystallizing resin should be higher than the softening point temperature of the first matrix resin. Typically, if the first matrix resin is PC, PC / ABS, or PC / ASA, at least one of the following high-temperature crystalline resins can be selected as the second matrix resin: polyphenylene sulfide (PPS), poly(1,4-cyclohexanedimethyl terephthalate) (PCT), or thermotropic liquid crystal polymer (TLCP); if the first matrix resin is SMA or TPU, at least one of the following high-temperature crystalline resins can be selected as the second matrix resin: polyhexamethylene adipate (PA66), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), or syndiotactic polystyrene (SPS); if the first matrix resin is polyphenylene ether (PPO), PAR, PSF, PES, or PPSU, the high-temperature crystalline resin polyether ether ketone (PEEK) can be selected as the second matrix resin.
[0030] Based on the total weight of the heat-resistant material, the amount of the second matrix resin is 2-15% by weight, preferably 3-12% by weight, and more preferably 5-10% by weight.
[0031] glass powder
[0032] The main components of the glass powder are at least one of the following: SiO2.P2O5, SiO2.B2O3, and SiO2.ZnO, with a particle size of 5–20 μm. Low-melting-point glass powder with a softening point temperature of 250–350 °C is preferred. Preferably, the low-melting-point glass powder used in this disclosure is pretreated with a coupling agent containing amino functional groups to obtain highly reactive low-melting-point glass powder. Coupling agents containing amino functional groups include γ-aminopropyltriethoxysilane (KH-550), 3-aminopropylmethyldiethoxysilane, 3-aminopropylmethyldimethoxysilane, N-β-(aminoethyl)γ-aminopropylmethyldiethoxysilane, etc., with KH-550 silane coupling agent being preferred.
[0033] Adding low-melting-point glass powder can further improve the dimensional stability of profiles. Due to its low melting temperature, the low-melting-point glass powder is uniformly dispersed in the matrix resin in a molten state after mixing and plasticizing. As the melt is extruded and gradually cooled and solidified, adjacent tiny glass melts bond together to form a highly rigid three-dimensional self-supporting network structure (ceramic skeleton). Because this ceramic skeleton itself has a very low coefficient of thermal expansion and ultra-high rigidity, it can significantly suppress dimensional changes in the resin matrix and greatly improve the dimensional stability of the profile.
[0034] Based on the total weight of the heat-resistant material, the amount of the low-melting-point glass powder is 2-25% by weight, preferably 2-20% by weight, and more preferably 4-15% by weight.
[0035] Expanded graphite
[0036] Expanded graphite is a porous carbon material with a high specific surface area. The expanded graphite used in this disclosure has a particle size of 50–100 mesh and an expansion ratio of 150–300 cm⁻¹. 3 / g, with an initial expansion temperature of 250–320℃. Preferably, the expanded graphite used in this disclosure is surface-activated using a coupling agent containing epoxy functional groups to obtain highly reactive expanded graphite. Coupling agents containing epoxy functional groups include 3(2,3-epoxypropoxy)propyltrimethoxysilane (KH-560), 3-(2,3-epoxypropoxy)propylmethyldiethoxysilane, 3(2,3-epoxypropoxy)propyltriethoxysilane, etc., with KH-560 silane coupling agent being preferred.
[0037] Expanded graphite exhibits different expansion ratios at different temperatures. Within the profile extrusion temperature range, expanded graphite possesses a micro-expansion function. Adding expanded graphite to the materials disclosed herein can effectively improve problems such as profile shrinkage and corner collapse. Simultaneously, during the twin-screw extrusion melt plasticizing stage, highly active cross-linking reactions can occur between the amino and epoxy groups on the surfaces of different powders, forming self-assembled composite powders in situ. Theoretically, this can form a highly rigid, three-dimensional self-supporting network-like structure. Expanded graphite can accumulate and distribute along this structure, forming a three-dimensional thermally conductive network-like structure, significantly improving the material's thermal conductivity, promoting uniform heat diffusion, and solving the deformation problem caused by uneven cooling of the inner and outer layers of the profile melt, especially at the corners and ribs of the profile. It also effectively reduces bending deformation along the length direction, thereby reducing the profile's curvature.
[0038] Based on the total weight of the heat-resistant material, the amount of expanded graphite is 0.1-20% by weight, preferably 1-10% by weight, and more preferably 2-8% by weight.
[0039] Optional adjuvants
[0040] Additives include, but are not limited to, compatibilizers, antioxidants, lubricants, anti-aging agents, crosslinking agents, co-crosslinking agents, and surfactants. There are no specific restrictions on the additives added to the heat-resistant materials disclosed herein; various commercially available additives can be used, as long as they do not limit the purpose of the invention.
[0041] In a specific embodiment of this disclosure, the additives include a compatibilizer, an antioxidant, and a lubricant. The compatibilizer is added to improve the compatibility between the first matrix resin and the second matrix resin. The lubricant reduces friction between molecules within the plastic, improves the processing performance of the plastic, and increases production efficiency. The antioxidant extends the service life of the material. In one embodiment of this disclosure, the compatibilizer includes at least one of styrene-maleic anhydride random copolymer (SMA), ethylene-methyl acrylate-glycidyl methacrylate terpolymer (EMA-g-GMA), maleic anhydride-grafted ethylene propylene diene monomer (EPDM-g-MAH), and maleic anhydride-grafted ethylene-1-octene copolymer (POE-g-MAH). In one embodiment of this disclosure, the antioxidant is antioxidant 1010; the lubricant is lubricant PETS.
[0042] Based on the total weight of the heat-resistant material, the amount of the additive is 0-10% by weight, preferably 0.1%-8% by weight, more preferably 1-10% by weight, the amount of the compatibilizer is 0.01-8% by weight, preferably 0.1%-5% by weight, more preferably 0.5-3% by weight, and the amount of the antioxidant and lubricant is 0.01-5% by weight, preferably 0.1%-2% by weight, more preferably 0.5-1% by weight.
[0043] In one specific embodiment of this disclosure, the weight ratio of the first matrix resin, the second matrix resin, the glass powder and the expanded graphite is (60-90):(2-15):(2-25):(0.1-20), preferably (62-88):(5-10):(4-15):(2-8).
[0044] In a preferred embodiment of this disclosure, the heat-resistant material comprises:
[0045]
[0046] Products
[0047] Various articles can be prepared using the heat-resistant materials described in this disclosure. Specifically, the articles are profiles prepared by extruding the heat-resistant materials described in this disclosure. The articles or profiles are used to contact, encapsulate, or partially encapsulate conductive metals.
[0048] A method for preparing profiles, the method comprising mixing and extruding a first matrix resin, a second matrix resin, glass powder, expanded graphite and optional additives to form a profile melt, and then cooling and shaping the profile melt to form a profile.
[0049] In a preferred embodiment, the method further includes pretreatment of glass powder and / or expanded graphite.
[0050] In a preferred embodiment, the pretreatment step includes pretreating the glass powder with a coupling agent containing amino functional groups.
[0051] In a preferred embodiment, the pretreatment step includes pretreating the expanded graphite with a coupling agent containing epoxy functional groups.
[0052] In a preferred embodiment, the pretreatment step includes pretreating the glass powder with a coupling agent containing amino functional groups and pretreating the expanded graphite with a coupling agent containing epoxy functional groups.
[0053] In a preferred embodiment, the method for preparing the profile includes mixing and extruding 60-90% by weight of a first matrix resin, 2-15% by weight of a second matrix resin, 2-25% by weight of low-melting-point glass powder pretreated with an amino-functional coupling agent, 0.1-20% by weight of expanded graphite pretreated with an epoxy-functional coupling agent, and 0-10% by weight of additives to form a profile melt, and then cooling and shaping the profile melt in a shaping mold to obtain the profile described in this disclosure.
[0054] In a preferred embodiment, the article or profile is in contact with a conductive metal, which is enclosed or partially enclosed in the article or profile.
[0055] In a preferred embodiment, the method includes the following steps:
[0056] 1) The hydrolyzed amino-functionalized silane coupling agent is mixed with low-melting-point glass powder and a coupling reaction is carried out to obtain low-melting-point glass powder pretreated with amino-functionalized coupling agent.
[0057] 2) The hydrolyzed epoxy-functionalized silane coupling agent is mixed with expanded graphite and subjected to a coupling reaction to obtain low-melting-point glass powder pretreated with epoxy-functionalized coupling agent.
[0058] 3) Mix the first matrix resin, the second matrix resin, the compatibilizer, the pretreated low-melting-point glass powder, the pretreated expanded graphite, the antioxidant, and the lubricant;
[0059] 4) The mixture obtained in step 3) is extruded through an extruder to form a profile melt;
[0060] 5) Cool and shape the molten profile obtained in step 4) in a shaping mold to form a profile.
[0061] Pretreatment, mixing, extrusion molding, and cooling / setting via coupling reaction can be carried out using methods and equipment known in the art. For example, the extrusion step can be performed using a twin-screw extruder, preferably a conical twin-screw extruder, and cooling / setting can be performed under vacuum conditions using a spray cooling device. Those skilled in the art can adjust the reaction conditions and equipment parameters based on their general technical knowledge, as long as the purpose of this disclosure is achieved.
[0062] The beneficial effects of this disclosure are as follows:
[0063] This disclosure selects an amorphous resin as the first matrix resin component and adds a high-temperature crystalline resin as the second matrix resin component. Simultaneously, low-melting-point glass powder and expanded graphite are added. The low-melting-point glass powder forms a highly rigid three-dimensional self-supporting network structure in the material, while the expanded graphite is enriched and distributed along the three-dimensional self-supporting network structure to form a three-dimensional thermally conductive network structure. This solves the problems of easy deformation and dimensional instability of profiles during extrusion. Profiles prepared using the heat-resistant material according to this disclosure method have advantages such as high heat resistance, good thermal conductivity, fast extrusion rate, strong high-temperature stability, and no deformation or collapse defects.
[0064] In this disclosure, the terms "contains," "comprises," or "uses" indicate that various ingredients may be used together in the mixtures or compositions of this disclosure. Therefore, the terms "consistent with..." and "composed of..." are included within the terms "contains," "comprises," or "uses." It should be understood that the degree of terms such as "high," "low," etc., used in this disclosure is well known in the art. For example, regarding "heat resistance," those skilled in the art, in conjunction with existing materials, can determine whether a material is heat-resistant.
[0065] Unless otherwise specified, all raw materials disclosed herein are commercially available or prepared according to conventional methods in the art. Unless otherwise defined or stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of skill in the art. Furthermore, any methods and materials similar to or equivalent to those described herein may be applied to the methods of this disclosure. Other aspects of this disclosure will be apparent to those skilled in the art from the content of this disclosure.
[0066] The present disclosure is further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the disclosure. Experimental methods in the following embodiments, unless specific conditions are specified, are generally determined according to national standards. If no corresponding national standard exists, then common international standards, conventional conditions, or conditions recommended by the manufacturer are followed. Unless otherwise stated, all parts are parts by weight, all percentages are weight percentages, and the molecular weight of the polymer is a number-average molecular weight.
[0067] Raw material sources and preparation:
[0068] PC resin, product name SC-1100R, purchased from Samsung Cheil Industries Co., Ltd. of South Korea;
[0069] PPS resin, product name HMR6002, was purchased from Sichuan Deyang Special New Materials Co., Ltd.
[0070] PCT resin, product grade 0502HC, was purchased from SK Chemicals Co., Ltd. in South Korea.
[0071] SMA resin, product name SMA-800, purchased from Jiaxing Huawen Chemical Co., Ltd.
[0072] PA66 resin, product grade EPR27, purchased from China Shenma Group Co., Ltd.
[0073] PET resin, product grade CZ-318, was purchased from Jiangsu Sanfangxiang Jucai Co., Ltd.
[0074] PAR resin, product name U8400, purchased from EUNICA Corporation, Japan;
[0075] PEEK resin, product grade 5600P, purchased from Shandong Junhao High Performance Polymer Co., Ltd.
[0076] Compatibilizer POE-g-MAH granules, product brand N406, were purchased from Ningbo Nengzhiguang New Material Technology Co., Ltd.
[0077] Compatibilizer EPDM-g-MAH granules, product brand N428, were purchased from Ningbo Nengzhiguang New Material Technology Co., Ltd.
[0078] Compatibilizer SMA granules, product brand SMA-700, were purchased from Jiaxing Huawen Chemical Co., Ltd.
[0079] Low melting point glass powder, product grade JP340, purchased from Shijiazhuang Luoma Special Glass Co., Ltd.
[0080] Expanded graphite, product brand KP250, purchased from Qingdao Tianyuanda Graphite Co., Ltd.
[0081] Antioxidant, product brand 1010, purchased from BASF AG;
[0082] Lubricant, product brand PETS-AF, purchased from FARK S.A., Italy;
[0083] The coupling agent KH550 is a γ-aminopropyltriethoxysilane coupling agent, purchased from Yunsheng Chemical (Shandong) Co., Ltd.
[0084] The coupling agent KH560 is a 3(2,3-epoxypropoxy)propyltrimethoxysilane coupling agent, purchased from Yunsheng Chemical (Shandong) Co., Ltd.
[0085] The ethanol solution was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., and was prepared by diluting it with water to the required mass concentration.
[0086] Product performance testing:
[0087] (1) Hot-ball pressure test:
[0088] The product's heat resistance was evaluated by testing the hot-ball pressure at 125°C according to the method described in GB / T 5169.21.
[0089] (2) Thermal conductivity test:
[0090] The thermal conductivity of the product was tested according to the method described in GB / T3399 to evaluate the product's heat dissipation performance.
[0091] (3) Dimensional change rate test:
[0092] The product's dimensional change rate (%) under repeated high and low temperatures was tested according to the method described in GB / T 8814 to assess the product's stability. The specific test steps are as follows:
[0093] 1) Cut three specimens with a length of (500±5) mm from the profile. The cut should be flat and perpendicular to the visible surface of the profile.
[0094] 2) Draw two lines with a spacing of 450 mm in the center of the visible surface of each sample, and conduct the experiment of repeated high and low temperatures 5 times, that is:
[0095] After maintaining the temperature at 23°C for 1 hour, the temperature was lowered to -20°C and maintained for 6 hours, then raised to 23°C and maintained for 1 hour, then raised to 63°C and maintained for 16 hours. After the experiment, the temperature was placed at 23°C for more than 12 hours, and the distance between the markings was measured to an accuracy of 0.1 mm.
[0096] 3) Formula for calculating the rate of dimensional change under repeated high and low temperatures:
[0097] △L=(L1-L0) / L0*100%
[0098] △L—Rate of dimensional change under repeated high and low temperatures, %;
[0099] L0—Distance between the markings before the experiment, mm;
[0100] L1—Distance between markings after the experiment, mm;
[0101] 4) The dimensional change rate under repeated high and low temperatures was taken as the maximum value of the change rates of the three samples;
[0102] (4) Bending test
[0103] According to the method described in GB / T 8814, take a 1m long profile sample, place the side of the sample parallel to the surface of the platform, measure the maximum distance between the bottom edge of the sample and the platform with a feeler gauge, and take the average value after three tests to test the bending deformation of the product.
[0104] (5) Testing for appearance defects such as shrinkage marks, deformation, and collapse
[0105] Product inspectors visually inspect the product to check for appearance defects such as shrinkage marks, deformation, and collapse. Specific Implementation
[0107] Example 1
[0108] The heat-resistant material is prepared and extruded to produce profiles using the following steps:
[0109] 1) Coupling agent hydrolysis:
[0110] 50 ml of amino-functionalized coupling agent KH550 was dispersed in 320 ml of 95% ethanol solution and stirred at 50°C for 30 min to obtain hydrolyzed KH550; 25 ml of epoxy-functionalized KH560 was dispersed in 160 ml of 95% ethanol solution and stirred at 50°C for 30 min to obtain hydrolyzed KH560.
[0111] 2) Powder activation:
[0112] 200g of low-melting-point glass powder was mixed with hydrolyzed KH-550 and stirred at 80℃ for 6 hours, then filtered. The filter residue was then washed three times with a 99.7% ethanol solution and dried to obtain low-melting-point glass powder with amino groups. 200g of expanded graphite was mixed with hydrolyzed KH-560 and stirred at 80℃ for 6 hours, then filtered. The filter residue was then washed three times with a 99.7% ethanol solution and dried to obtain expanded graphite with epoxy groups.
[0113] 3) Material mixing:
[0114] Weigh the following materials according to the following weight proportions: 75.5 parts of PC resin (first matrix), 5 parts of PPS resin (second matrix), 2 parts of POE-g-MAH granules (compatibilizer), 15 parts of low-melting-point glass powder with amino groups, 2 parts of expanded graphite with epoxy groups, and 0.5 parts of lubricant and antioxidant. Add the above materials together to a high-speed mixer (GX-200, Zhangjiagang Tongsha Plastic Machinery Co., Ltd.) and mix for 3 minutes to obtain a mixture.
[0115] 4) Twin-screw extrusion:
[0116] The mixed material is added to the hopper of a conical twin-screw extruder (SJSZ65, Zhangjiagang Tongsha Plastic Machinery Co., Ltd.), where it is melted and plasticized before being extruded through a die. The process parameters of the twin-screw extruder are as follows: Zone 1 temperature 240℃, Zone 2 temperature 250℃, Zone 3 temperature 260℃, Zone 4 temperature 270℃, Zone 5 temperature 270℃, Zone 6 temperature 270℃, Zone 7 temperature 270℃, Zone 8 temperature 270℃, Zone 9 temperature 275℃, die temperature 285℃, and the twin-screw extruder speed is 150 r / min.
[0117] 5) Cooling, shaping, and cutting:
[0118] The molten profile is cooled and shaped by a vacuum cooling and shaping mold and a mist spray cooling device, and then cut and bundled by a traction machine (WWSJ-1000, Wanwei Plastic Machinery Co., Ltd.).
[0119] Example 2:
[0120] The heat-resistant material is prepared and extruded to produce profiles using the following steps:
[0121] 1) Coupling agent hydrolysis:
[0122] 50 ml of KH550 was dispersed in 320 ml of 75% ethanol solution and stirred at 60°C for 20 min to obtain hydrolyzed KH550; 25 ml of KH560 was dispersed in 160 ml of 75% ethanol solution and stirred at 60°C for 20 min to obtain hydrolyzed KH560.
[0123] 2) Powder activation:
[0124] 200g of low-melting-point glass powder was mixed with hydrolyzed KH-550 and stirred at 15℃ for 10 hours, then filtered. The filter residue was then washed three times with a 99.7% ethanol solution and dried to obtain low-melting-point glass powder with amino groups. 200g of expanded graphite was mixed with hydrolyzed KH-560 and stirred at 15℃ for 10 hours, then filtered. The filter residue was then washed three times with a 99.7% ethanol solution and dried to obtain expanded graphite with epoxy groups.
[0125] 3) Material mixing:
[0126] Weigh the following materials according to the following weight proportions: 76.5 parts of PC resin (first matrix), 10 parts of PPS resin (second matrix), 0.5 parts of EPDM-g-MAH granules (compatibilizer), 4 parts of low-melting-point glass powder with amino groups, 8 parts of expanded graphite with epoxy groups, and 1 part of lubricant and antioxidant. Add the above materials together to a high-speed mixer and mix for 5 minutes to obtain a mixture.
[0127] 4) Twin-screw extrusion:
[0128] The mixed material is added to the hopper of a conical twin-screw extruder, melted and plasticized by the twin-screw extruder, and then extruded through the die to form the final shape. The process parameters of the twin-screw extruder are: zone 1 temperature 245℃, zone 2 temperature 255℃, zone 3 temperature 265℃, zone 4 temperature 275℃, zone 5 temperature 275℃, zone 6 temperature 275℃, zone 7 temperature 275℃, zone 8 temperature 275℃, zone 9 temperature 280℃, die temperature 290℃, and the twin-screw extruder speed is 200 r / min.
[0129] 5) Cooling, shaping, and cutting:
[0130] The molten profile is cooled and shaped by a vacuum cooling and shaping mold and a mist spray cooling device, and then cut and bundled by a traction machine.
[0131] The machine model used in Example 2 is the same as that in Example 1.
[0132] Example 3:
[0133] The heat-resistant material is prepared and extruded to produce profiles using the following steps:
[0134] 1) Coupling agent hydrolysis:
[0135] 50 ml of KH550 was dispersed in 320 ml of 85% ethanol solution and stirred at 40°C for 40 min to obtain hydrolyzed KH550; 25 ml of KH560 was dispersed in 160 ml of 85% ethanol solution and stirred at 40°C for 40 min to obtain hydrolyzed KH560.
[0136] 2) Powder activation:
[0137] 200g of low-melting-point glass powder was mixed with hydrolyzed KH-550 and stirred at 50℃ for 5 hours, then filtered. The filter residue was then washed three times with a 99.7% ethanol solution and dried to obtain low-melting-point glass powder with amino groups. 200g of expanded graphite was mixed with hydrolyzed KH-560 and stirred at 50℃ for 5 hours, then filtered. The filter residue was then washed three times with a 99.7% ethanol solution and dried to obtain expanded graphite with epoxy groups.
[0138] 3) Material mixing:
[0139] Weigh the following materials according to the following weight proportions: 74 parts of PC resin (first matrix), 9 parts of PPS resin (second matrix), 3 parts of SMA granules (compatibilizer), 9 parts of low-melting-point glass powder with amino groups, 5 parts of expanded graphite with epoxy groups, and 1 part of lubricant and antioxidant. Add the above materials together to a high-speed mixer and mix for 4 minutes to obtain a mixture.
[0140] 4) Twin-screw extrusion:
[0141] The mixed material is added to the hopper of a conical twin-screw extruder, melted and plasticized by the twin-screw extruder, and then extruded through the die to form the final shape. The process parameters of the twin-screw extruder are: zone 1 temperature 242℃, zone 2 temperature 252℃, zone 3 temperature 262℃, zone 4 temperature 272℃, zone 5 temperature 272℃, zone 6 temperature 272℃, zone 7 temperature 272℃, zone 8 temperature 272℃, zone 9 temperature 278℃, die temperature 288℃, and the twin-screw extruder speed is 160 r / min.
[0142] 5) Cooling, shaping, and cutting:
[0143] The molten profile is cooled and shaped by a vacuum cooling and shaping mold and a mist spray cooling device, and then cut and bundled by a traction machine.
[0144] The machine model used in Example 3 is the same as that in Example 1.
[0145] Example 4:
[0146] Example 4 was carried out using the raw materials and method described in Example 3, the only difference being that the second matrix resin in this example was PCT resin. The process parameters of the twin-screw extruder were: zone 1 temperature 240℃, zone 2 temperature 250℃, zone 3 temperature 260℃, zone 4 temperature 273℃, zone 5 temperature 275℃, zone 6 temperature 275℃, zone 7 temperature 275℃, zone 8 temperature 275℃, zone 9 temperature 278℃, die temperature 290℃, and the twin-screw extruder speed was 180 r / min.
[0147] Example 5:
[0148] Example 5 was carried out using the raw materials and method described in Example 3, the only difference being that the first matrix resin in this example was SMA resin, and the second matrix resin was PA66 resin. The process parameters of the twin-screw extruder were: zone 1 temperature 210℃, zone 2 temperature 225℃, zone 3 temperature 235℃, zone 4 temperature 245℃, zone 5 temperature 245℃, zone 6 temperature 245℃, zone 7 temperature 245℃, zone 8 temperature 245℃, zone 9 temperature 255℃, die temperature 265℃, and the twin-screw extruder speed was 170 r / min.
[0149] Example 6:
[0150] Example 6 was carried out using the raw materials and method described in Example 3, with the only difference being that the first matrix resin in this example was TPU resin, and the second matrix resin was PET resin. The process parameters of the twin-screw extruder were: zone 1 temperature 215℃, zone 2 temperature 220℃, zone 3 temperature 230℃, zone 4 temperature 242℃, zone 5 temperature 242℃, zone 6 temperature 242℃, zone 7 temperature 242℃, zone 8 temperature 242℃, zone 9 temperature 252℃, die temperature 262℃, and the twin-screw extruder speed was 120 r / min.
[0151] Example 7:
[0152] Example 7 was carried out using the raw materials and method described in Example 3, the only difference being that the first matrix resin in this example was PAR resin, and the second matrix resin was PEEK resin. The process parameters of the twin-screw extruder were: zone 1 temperature 295℃, zone 2 temperature 300℃, zone 3 temperature 310℃, zone 4 temperature 320℃, zone 5 temperature 330℃, zone 6 temperature 330℃, zone 7 temperature 330℃, zone 8 temperature 335℃, zone 9 temperature 345℃, die temperature 350℃, and the twin-screw extruder speed was 190 r / min.
[0153] Example 8:
[0154] Example 8 was carried out according to the raw materials and methods described in Example 3. The only difference from Example 3 was that the low melting point glass powder and expanded graphite were not activated in this example.
[0155] Comparative Example 1:
[0156] Comparative Example 1 was carried out according to the raw materials and methods described in Example 3. The only difference from Example 3 was that no second matrix resin component was added in this comparative example, while the proportions of other components remained unchanged.
[0157] Comparative Example 2:
[0158] Comparative Example 2 was carried out according to the raw materials and methods described in Example 3. The only difference from Example 3 was that no low melting point glass powder component was added in this comparative example, while the proportions of other components remained unchanged.
[0159] Comparative Example 3:
[0160] Comparative Example 3 was carried out using the raw materials and methods described in Example 3. The only difference from Example 3 was that no expanded graphite component was added in this comparative example, while the proportions of other components remained unchanged.
[0161] Comparative Example 4:
[0162] Comparative Example 4 was carried out according to the raw materials and methods described in Example 3. The only difference from Example 3 was that low melting point glass powder and expanded graphite were not added in this comparative example, while the proportions of other components remained unchanged.
[0163] The plastic granules prepared in Examples 1-8 and Comparative Examples 1-4 were injection molded into strips or templates for physical property testing. The test results are shown in Table 1.
[0164] Table 1 Test Results
[0165]
[0166]
[0167] In Table 1, the profiles prepared in Examples 1-8 of this disclosure exhibit strong forming ability, with maximum extrusion speeds all exceeding 4.5 m / min. This is because Examples 1-8 added a highly crystalline second matrix component, which allows for rapid cooling and shaping, significantly increasing the extrusion speed. In contrast, Comparative Example 1, which did not add highly crystalline resin, had a maximum extrusion speed of only 2 m / min, significantly lower than Examples 1-8. The profiles prepared in Examples 1-8 of this disclosure demonstrate excellent dimensional stability. This is because the three-dimensional self-supporting network structure formed by the low-melting-point glass powder effectively suppresses dimensional changes in the profiles. In particular, the dimensional change rate of Examples 1-7, which used pretreated low-melting-point glass powder, did not exceed 0.22% during repeated high and low temperature cycles. In contrast, the profiles prepared in Comparative Examples 2 and 4, which did not add low-melting-point glass powder, exhibited poor dimensional stability, with dimensional change rates of 0.7% and 0.8% during repeated high and low temperature cycles, respectively. The profiles prepared in Examples 1-8 showed no shrinkage, deformation, or corner collapse. This is because, in addition to its micro-expansion function during the profile extrusion process, expanded graphite also possesses excellent thermal conductivity and forms a relatively complete three-dimensional thermally conductive network structure. This allows for excellent thermal conductivity even at low addition levels, which facilitates uniform heat dissipation during cooling and reduces profile bending deformation. The results from Examples 1-7 and Example 8 demonstrate that using pretreated low-melting-point glass powder and pretreated expanded graphite provides better thermal conductivity and molding stability.
[0168] The above description is merely a preferred embodiment of this disclosure and is not intended to limit the scope of the substantive technical content of this disclosure. The substantive technical content of this disclosure is broadly defined within the scope of the claims of this application. Any technical entity or method completed by others that is completely identical to or an equivalent modification of the claims of this application shall be deemed to be covered within the scope of the claims.
[0169] All documents mentioned in this disclosure are incorporated herein by reference as if each document were individually incorporated herein by reference. Furthermore, it should be understood that after reading the foregoing contents of this disclosure, those skilled in the art can make various alterations or modifications to this disclosure, and these equivalent forms also fall within the scope defined by the appended claims.
Claims
1. A heat-resistant material comprising a first matrix resin, a second matrix resin, glass powder, expanded graphite, and optional additives, wherein the first matrix resin is at least one amorphous resin selected from the group consisting of: polycarbonate, polyphenylene ether, polycarbonate and acrylonitrile-styrene-butadiene copolymer alloy, polycarbonate and acrylonitrile-styrene-acrylate copolymer alloy, styrene-maleic anhydride random copolymer, engineering plastic grade polyurethane, poly(4,4-isopropylidene biphenylene terephthalate / isophthalate copolymer, bisphenol A type polysulfone, polyethersulfone, and polyphenylene sulfone; The second matrix resin is at least one high-temperature crystalline resin selected from the group consisting of: polyphenylene sulfide, poly(1,4-cyclohexanedimethyl terephthalate), thermotropic liquid crystal polymer, polyhexamethylene adipamide, polyethylene terephthalate, polyethylene naphthalate, syndiotactic polystyrene, and polyetheretherketone. The glass powder is a low melting point glass powder with a softening point temperature of 250-350℃. Based on the total weight of the heat-resistant material, the amount of the first matrix resin is 60-90% by weight, the amount of the second matrix resin is 2-15% by weight, the amount of the low melting point glass powder is 2-25% by weight, the amount of the expanded graphite is 0.1-20% by weight, and the amount of the additives is 0-10% by weight.
2. The heat-resistant material as described in claim 1, characterized in that, The additives include compatibilizers, antioxidants, and lubricants.
3. The heat-resistant material as described in claim 1, characterized in that, The main components of the glass powder are at least one of the following: SiO2.P2O5, SiO2.B2O3 and SiO2.ZnO, with a particle size of 5 to 20 μm.
4. The heat-resistant material as described in claim 1, characterized in that, The expanded graphite has a particle size of 50-100 mesh, an expansion ratio of 150-300 cm³ / g, and an initial expansion temperature of 250-320℃.
5. The heat-resistant material as described in claim 1, characterized in that, The glass powder is pretreated with a coupling agent containing amino functional groups; and / or the expanded graphite is pretreated with a coupling agent containing epoxy functional groups.
6. The heat-resistant material as described in claim 5, characterized in that, The coupling agents containing amino functional groups include γ-aminopropyltriethoxysilane, 3-aminopropylmethyldiethoxysilane, 3-aminopropylmethyldimethoxysilane, and N-β-(aminoethyl)γ-aminopropylmethyldiethoxysilane; and / or the coupling agents containing epoxy functional groups include 3(2,3-epoxypropoxy)propyltrimethoxysilane, 3-(2,3-epoxypropoxy)propylmethyldiethoxysilane, and 3(2,3-epoxypropoxy)propyltriethoxysilane.
7. An article prepared using the heat-resistant material according to any one of claims 1-6.
8. The article of claim 7, characterized in that, The product is a profile obtained by extruding heat-resistant material.
9. The article of claim 7, characterized in that, The article is in contact with a conductive metal, and the conductive metal is wrapped or partially wrapped in the article.
10. A method for preparing a profile, the method comprising mixing and extruding a first matrix resin, a second matrix resin, glass powder, expanded graphite, and optional additives to form a profile melt, and then cooling and shaping the profile melt in a molding die, wherein the first matrix resin is at least one amorphous resin selected from the group consisting of: polycarbonate, polyphenylene ether, polycarbonate and acrylonitrile-styrene-butadiene copolymer alloy, polycarbonate and acrylonitrile-styrene-acrylate copolymer alloy, styrene-maleic anhydride random copolymer, engineering plastic grade polyurethane, poly(4,4-isopropylidene biphenylene terephthalate / isophthalate copolymer, bisphenol A type polysulfone, polyethersulfone, and polyphenylene sulfone; The second matrix resin is at least one high-temperature crystalline resin selected from the group consisting of: polyphenylene sulfide, poly(1,4-cyclohexanediol) terephthalate, thermotropic liquid crystal polymer, polyhexamethylene adipamide, polyethylene terephthalate, polyethylene naphthalate, syndiotactic polystyrene, and polyetheretherketone; the glass powder is a low-melting-point glass powder with a softening point temperature of 250–350°C; based on the total weight of the heat-resistant material, the amount of the first matrix resin is 60–90% by weight, the amount of the second matrix resin is 2–15% by weight, the amount of the low-melting-point glass powder is 2–25% by weight, the amount of expanded graphite is 0.1–20% by weight, and the amount of the additives is 0–10% by weight.
11. Use of a combination of glass powder and expanded graphite in improving the extrusion stability and / or molding capability of a material, wherein the glass powder is a low-melting-point glass powder with a softening point temperature of 250–350°C, and the material comprises a first matrix resin and a second matrix resin, wherein the first matrix resin is at least one amorphous resin selected from the group consisting of: polycarbonate, polyphenylene ether, polycarbonate and acrylonitrile-styrene-butadiene copolymer alloy, polycarbonate and acrylonitrile-styrene-acrylate copolymer alloy, styrene-maleic anhydride random copolymer, engineering plastic grade polyurethane, poly(4,4-isopropylidene biphenylene terephthalate / isophthalate copolymer, bisphenol A type polysulfone, polyethersulfone, and polyphenylene sulfone; and the second matrix resin is at least one high-temperature crystalline resin selected from the group consisting of: polyphenylene sulfide, poly(1,4-cyclohexanedimethyl terephthalate), thermotropic liquid crystal polymer, polyhexamethylene adipamide, polyethylene terephthalate, polyethylene naphthalate, syndiotactic polystyrene, and polyetheretherketone.
Citation Information
Patent Citations
Fireproof expanding low-smoke halogen-free flame-retardant sheath material and preparation method thereof
CN106750855A
